Who Speaks for Whom? Interest Representation for Non-Standard Employees - Czarzasty, Jan (Warsaw Forum of Economic Sociology, 2016)
The paper concentrates on the issues of interest representation for non-standard employees. The empirical findings from the European Union (EU) level are used as a frame of reference for analysis of the situation in Poland. Nonstandard employment is an ambiguous notion, so is, naturally, the concept of non-standard workers. In Poland nonstandard employment has been growing, mostly in a form of 'junk jobs'. Trade unions, and other institutional forms of collective interest representation, struggle to endorse problems faced by non-standard employees, with a moderate degree of success.